Landscape, Language and Interiority in Modern Haiku - Jorge, Julia (Mirai. Estudios Japoneses, 2022)
This paper examines the transformations of haiku since the beginning of the twentieth century. Based on Karatani Kojin’s theorization of the discovery of landscape and interiority, this work extends to the discovery of language. This paper reviews the incidence of these three phenomena in the most representative Japanese haiku poetics of the beginning of the century in order to demonstrate that these transformations were decisive for the definition of modern haiku